Knowledge and practice of preconception health, perception and experience of utilising preconception care and its association with early antenatal booking among women with high risk pregnancy in Kinta District, Perak - Jusoh, Nazirah (2018)
Knowledge and practice of preconception health, perception and experience of utilising preconception care and its association with early antenatal booking among women with high risk pregnancy in Kinta District, Perak. Preconception care is a promising new approach to improve the health of future children through primary intervention and to ensure appropriate action and avoid risks in early pregnancy. A greater number of women are being categorized as high risk pregnancies due to shift in maternal age and obesity prevalence. This study aims to determine the preconception health knowledge and practice, factors associated with early antenatal booking and to explore the experiences and perceptions of preconception care among antenatal women with high risk pregnancy in Kinta District, Perak. This is a mixed-method study comprising of a quantitative crosssectional survey and an exploratory qualitative study. A cross-sectional survey was conducted between March and December 2016 at 14 health clinics in Kinta District, Perak. Women who came for their first antenatal booking were randomly selected. A validated interviewer guided questionnaire was administered. It consisted of three domains, assessing sociodemographic data, knowledge and practice of preconception care. Knowledge score of more than 12 was categorized as good knowledge, and practice score of more than 8 was considered as good preconception practice. The qualitative study using focus group discussion and in-depth interview were conducted among women with high risk pregnancy selected through purposive sampling among those who had participated in the quantitative survey. A total of 490 respondents participated in the study. The mean age was 29.9 (SD 5.56) years old. Majority of respondents were Malay 347 (70.8%). Only 23.9% of respondents attended preconception care. About 48.6% of the respondents had good knowledge and 76.7% had good practice of preconception health. The proportion of those who attended early antenatal booking was 74.3%. The significant factors found to be associated with early antenatal booking were women who attended preconception care (Adj. OR: 1.54; 95% CI: 1.30, 3.98; p=0.043), planned pregnancy (Adj. OR: 2.21; 95% CI: 1.42, 3.45; p<0.001) and preconception health practice (Adj. OR: 1.88; 95% CI: 1.17, 3.01; p=0.009). There were three major themes emerged from the interview which are: women’s perceived preconception care is for family planning, preconception care is indicated for women with high risk pregnancy and preconception care as for preparation for the next pregnancy. Women who attended preconception care experienced long waiting time from the registration to the consultation, lack of privacy and confidentiality, and preferred to be seen by female doctors. Proportion of antenatal women with high risk pregnancy who attended preconception care were low and they had fair knowledge on preconception health. Most of the respondents’ perception of preconception care was incomplete. Strategies should focus on improving the low level of knowledge as well as misconception about preconception care as identified in this study.